1998
DOI: 10.1111/j.1600-0625.1998.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the immunoultrastructural organization of cutaneous basement membrane zone molecules

Abstract: The epidermal basement membrane zone (BMZ) is composed of various molecules, each of which plays an important role in dermoepidermal adhesion. Genetic abnormality of certain BMZ molecules leads to an inherited group of skin diseases collectively referred to as epidermolysis bullosa, whose hallmark is skin fragility of varying degrees. Furthermore, development of autoantibodies to certain BMZ molecules leads to the onset of a number of acquired autoimmune blistering diseases in which dermo-epidermal separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Histologically, subepidermal blisters associated with inflammatory cell infiltration in the dermis are observed. BP is induced by autoantibodies against type XVII collagen (COL17, also called BP180 and BPAG2), a hemidesmosomal type II transmembrane protein that spans the lamina lucida and projects into the lamina densa of the dermal/epidermal junction (DEJ) (1)(2)(3)(4). Studies to map the epitopes on COL17 have revealed that the juxtamembranous extracellular noncollagenous 16A domain (NC16A) is preferentially recognized by autoantibodies in the sera of BP patients (5,6).…”
mentioning
confidence: 99%
“…Histologically, subepidermal blisters associated with inflammatory cell infiltration in the dermis are observed. BP is induced by autoantibodies against type XVII collagen (COL17, also called BP180 and BPAG2), a hemidesmosomal type II transmembrane protein that spans the lamina lucida and projects into the lamina densa of the dermal/epidermal junction (DEJ) (1)(2)(3)(4). Studies to map the epitopes on COL17 have revealed that the juxtamembranous extracellular noncollagenous 16A domain (NC16A) is preferentially recognized by autoantibodies in the sera of BP patients (5,6).…”
mentioning
confidence: 99%
“…11 In patients with BP, the target epitopes for BMZ antibodies are located on the NC16A domain of BP180 antigen, ultrastructurally localized in the upper part of the lamina lucida, whereas the serum samples of most patients with MMP recognize the carboxyterminal domain of BP180 antigen at the lamina lucida-lamina densa border. 12 In some patients with MMP, autoantibodies are directed against the ␣ chain of laminin 5, localized in the upper part of the lamina densa.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is because of the presence of 2 different targeted antigens recognized in the serum samples of patients with MMP: the C domain of BP180 antigen, present in the lower part of the lamina lucida; and laminin 5 (also known as epiligrin), localized in the upper part of the lamina densa. 11,22,23 Thus, a direct salt-split pattern cannot be conclusive in patients with MMP.…”
Section: Commentmentioning
confidence: 99%
“…Like other collagens, the molecule is able to trimerize by self assembly in such a way that the extracellular fragment forms a triple helix, ␣1[XVII] 3 (Balding et al, 1997;Hirako et al, 1996;Pas et al, 1999). The length of the rod domain is sufficient to traverse the lamina lucida, and the flexible carboxyl terminus has been seen within the lamina densa (Shimizu, 1998). Its as yet unidentified ligand(s) may reside within the lamina densa or lamina lucida.…”
mentioning
confidence: 99%
“…Its as yet unidentified ligand(s) may reside within the lamina densa or lamina lucida. A candidate ligand is laminin 5, which is mainly localized in the upper lamina densa (Shimizu, 1998). An interaction between the extracellular domain of type XVII collagen and laminin 5 has been reported (Reddy et al, 1998).…”
mentioning
confidence: 99%